Rituximab Therapy in Adults with Refractory Symptomatic Immune Thrombocytopenia: Long-Term Follow-Up of 15 Cases - Hindilerden, Fehmi (Turk J Haematol, 2017)
OBJECTIVE: This paper prospectively evaluates the long-term follow-up [mean ± standard deviation (SD) duration: 89.7±19.4 months] data of 15 patients (13 females and 2 males) with refractory symptomatic immune thrombocytopenia (ITP) treated with rituximab. MATERIALS AND METHODS: Rituximab was administered at 375 mg/m2 weekly for a total of 4 doses. Complete response (CR) was defined as a platelet count of ≥100,000/mm(3) and partial response (PR) as a platelet count of ≥30,000/mm(3) but less than 100,000/mm(3). Early response (ER) and late response (LR) were defined as response within 42 days and after 42 days of initiation of rituximab therapy, respectively. Sustained response (SR) was defined as response lasting for at least 6 months. RESULTS: Mean age (±SD) at the start of rituximab was 46.6±11.3 years. Mean platelet count (±SD) prior to rituximab treatment was 17,400±8878/mm(3). The mean time (±SD) between rituximab therapy and response to rituximab in early responders and late responders was 1.8±1.3 weeks and 10±2.8 weeks, respectively. Mean durations (±SD) of ER and LR were 51±47.2 months and 6±4.2 months, respectively. Seven of the 15 patients (46.7%) showed an initial response to rituximab (5 ER and 2 LR). The rate of SR over 6 months was 26.7% (4/15). Among the responders to rituximab, 3 (3/7, 42.9%) maintained their response 1 year after rituximab treatment and 2 (2/7, 28.6%) had ongoing response 5 years after initiation of rituximab. Two of the 7 patients (28.6%) still maintained their response 98 months after initiation of rituximab. All 5 initial responders with subsequent relapse achieved response from subsequent treatment modalities (3 CR, 2 PR). CONCLUSION: Our data confirm, over a long period of observation, that rituximab is safe and effective in the management of patients with chronic refractory primary ITP.